Sosialisasi Digital Marketing Dalam Upaya Mengoptimalkan Nilai Jual Produk UMKM Desa Kalisat - Dina Febriani; Moh Faizin; Clarinda Sevians Enjelita (Jumat Ekonomi: Jurnal Pengabdian Masyarakat, 2024)
Digital marketing also known as online marketing or internet marketing, refers to the promotional activities or campaingns undertaken to promote a brand or product through digital or online media with the aim of attracting consumers quickly. Digital marketing facilitates businesses in monitoring and catering to the needs and desires of potential consumers. On the other hand, potential consumers can also search for and obtain product information by simply browsing the virtual worls, thus streamlining the search process. In the endeavor, the asset baed community development approach is employed, emphasizing the development of existing assets and potentials with in a particular area. Specifically, in the vilage of Kalisat. Bungkal sub-district, Ponorogo regency, the local community possesses several micro, small, anad medium-sized enterprises owned by individuals or groups. Through the dissemination of digital marketing strategies, it is expected that the value and marketability of these products can be enhanced or optimized.